Motion Response Analysis of Hexagonal Pontoon Wave Energy Converter - Irfan Arief Syarief; Achmad Baidowi; Azzahra Nirwana Islami (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2020)
The wave energy conversion system is one of the technology innovative used in the researches of alternative power plant at sea. It receives environmental loads such as wave, wind, and current during its operation. In order to be able to rotate the pendulum and produce electricity, it is designed with a hexagonal shaped ponton with three floaters on its sides to increase the rotational motion of the ponton. These floaters are connected to the ponton by an arm, identically distance from one another. Mooring system used in this research is designed to allow it to still move and rotate the pendulum while keeping the platform from capsizing. This research is discussing about the difference of motion response between three variations of wave energy conversion system designs, Variation 1 that is designed with floaters, Variation 2 with shortened floater arms, and Variation 3 which have no floaters, by comparing their RAOs (Response Amplitude Operator), to figure out which design is the most responsive when collinear load from heading 0o, 30o, 60o, 90o, and 120o is acting on it. This research reveals that model Variation 1 is the most optimal because it has relatively higher values of RAOs, and the motion response of the ponton is still apparent after mooring system is installed. The highest RAO in free floating condition for 6 degree of freedom surge, sway, heave, pitch, roll, and yaw are 1,949 m/m frequency 0,1 Rad/s heading 0o, 1,6 m/m frequency 1,7 Rad/s heading 60o, 0,998 m/m frequency 0,1 Rad/s heading 0o, 22,13 Deg/m frequency 1,8 Rad/s heading 60o, 21,7 Deg/m frequency 2 Rad/s heading 0o, and 77,212 deg/m frequency 1,8 deg/m heading 0oconsecutively. The furthest excursion is at 5,1 meters along x-axis 0o load, while the shortest excursion is 1,5 meters along y-axis 120o load. The highest Roll motion reached 62,5o along the x-axis 90o load while pitch motion reached 15,5o along y-axis 120o load.